Managing Sustainable Development through Governance and Health Indicators: A Strategic Analysis using Dynamic ARDL for the U.S. - Alsulamy, Nouf Awadallah (International Journal of Economics and Financial Issues, 2025)
The study contributes the literature by examining the impact of life expectancy and governance indicators to achieve sustainable objectives in the US. For empirical estimations, we have used the dynamic autoregressive distributed lagged model. We have used three base models with economic growth, carbon emission and human development as dependent variables. Life expectancy reports positive coefficients for carbon emission and human development. The results mention that higher life expectancy causes environmental degradation. However, it enhances the human development indicators. As far as sustainable economic growth, life expectancy has confirmed the insignificant relationship. In light of governance indicators, governance effectiveness helps to reduce carbon emission. Regulatory quality has mentioned positive coefficients, indicating the significance of improving human development indicators. In concise, life expectancy and governance indicators influence the sustainable environment and human development, while sustainable economic growth is insignificant. The findings propose important policy implications to enhance the environmental and human quality.